Immunologial Study of IL32-gamma in Different Hepatitis B Virus Patient Groups at Alnajaf City - Ayat Hussein Shubbar; Fahem M. D (Institute of Medico-legal Publications Pvt Ltd, 2021)
Hepatitis B virus is a member of the Hepadnaviridae family and responsible for causing acute and chronichepatitis in humans. This review deals with our current understanding of the virology, life cycle andimmunopathology effecting of this very important pathogen. the present study show the relationship betweenHBV infection and the rule of IL32 gamma against it ,all of which are considered essential for current andfuture approaches to antiviral treatment. The study was conducted on 159 patients [ 43(53.75%) males and37(46.25%) females] during December ,2019 to July 2020 at AL-Najaf province. They suffering from signsand symptoms of liver diseases.